ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS NASABAH PEMBIAYAAN MURABAHAH PADA BANK PEMBIAYAAN RAKYAT SYARI’AH ADECO LANGSA - febi febi; Ndaru Irawadi; Abdul Hamid; Zikriatul Ulya (Jurnal Investasi Islam, 2019)
This study aimed to ﬁ nd out factors that inﬂ uencing costumers loyalty about murabahah ﬁ nancing at Bank Pembiayaan Rakyat Syariah Adeco Langsa and to determine the effects partialy and silmutanously to murabahah ﬁ ancing costumers loyalty. There are factors that inﬂ uencing murabahah ﬁ nancing costumers loyalty including the inﬂ uence of service factors, facility factors, and location factors. This study used the quantitative approach. The total of respondent are 80 costumers. Sampling this study was carried through probability sampling and simple random sampling , rarely the technique of determining to selected sample without regard to the levels in the population. This study used quesioners as many as 20 items questions that were assesed with a likert 1-5 scale and used validity and reliability test. The test of assumptions were, tests of multicollinearity, heteroscedastisitas, normality, linearity then analyzed using multiple regression analysis with the determination test method F test and t test. Base on multiple regression analysis at 5% signiﬁ cance level show that simultaneously service factors, facility factors, and location factors have signiﬁ cant positive effect to murabahah ﬁ nancing costumers loyalty at Bank Pembiayaan Rakyat Syariah Adeco Langsa, and then there are signiﬁ cant positive effect of the facility factors to murabahah ﬁ nancing costumer loyalty and the location also has a signiﬁ cant positive inﬂ uence on murabahah ﬁ nancing costumer loyalty at Bank Pembiayaan Rakyat Syariah Adeco Langsa, facility factor have the most dominant inﬂ uence on murabahah ﬁ nancing costumer loyalty at Bank Pembiayaan Rakyat Syariah Adeco Langsa, with a signiﬁ cance of 0,000 less than 0,05.